2020
DOI: 10.1002/nop2.558
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the barriers of adherence to dietary recommendations among patients with type 2 diabetes: A qualitative study in Iran

Abstract: Type II diabetes (T2D) is a major global health problem (Banerjee, Nema, Dhas, & Mishra, 2017), and its prevalence is rapidly increasing throughout the world (Hu et al., 2015). According to an International Diabetes Federation (IDF) report, 382 million adults in the world had diabetes in 2013 (Han, Kim, Kim, Lee, & Cho, 2017) and this figure is expected to reach 592 million by 2035 (Guariguata et al., 2014). The mentioned statistic also suggests that most of the diabetes patients will have T2D (Han et al., 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Unhealthy eating habits among type 2 diabetes are a significant impact in Bangladeshi [ 55 ]. A qualitative study in Iran documented that the food culture largely affects a type 2 DM patient’s adherence to a healthy diet [ 56 ]. In Ethiopia, the probable because of (a) low dietary adherence is economic burden of diabetes care is very disastrous among the less privileged populations group [ 57 ] (b) no access of healthy dietary habit [ 7 , 58 ] (c); and not access of recommended diet [ 59 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Unhealthy eating habits among type 2 diabetes are a significant impact in Bangladeshi [ 55 ]. A qualitative study in Iran documented that the food culture largely affects a type 2 DM patient’s adherence to a healthy diet [ 56 ]. In Ethiopia, the probable because of (a) low dietary adherence is economic burden of diabetes care is very disastrous among the less privileged populations group [ 57 ] (b) no access of healthy dietary habit [ 7 , 58 ] (c); and not access of recommended diet [ 59 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…The standard of care for diabetes mellitus patients includes management of diet, activity, medication, and glycemic control [24], [25]. The results of previous studies show that it is difficult for patients to undergo such treatment, so they need support from various parties, one of which is from their family [26], [27], [28], [29], [30].…”
Section: Discussionmentioning
confidence: 99%
“…Family support received by the patients will increase patient compliance in their care at home [10], [31]. The assistance needed by diabetes mellitus patients at home includes diet [30], [32] assistance for daily activities, health care, financial support, attention, and problem solving [32] as well as in activities, blood glucose monitoring, and medication [33]. Diabetes mellitus patients who get support from their families feel better due to emotional and behavioral support [34].…”
Section: Discussionmentioning
confidence: 99%
“…Similar to other East Asian countries, carbohydrates occupy a very important place in the traditional Chinese diet [19,20]. And it has shown that ingrained eating attitudes and habits is difficult to be changed [21,22]. Therefore, almost all caregivers expressed their confusion and worry when the dietary advice provided by the doctor was in strong conflict with the traditional diet.…”
Section: Discussionmentioning
confidence: 99%